Systematic review on diabetes mellitus and dental implants: an update - Juliane Wagner; Johannes H. Spille; Jörg Wiltfang; Hendrik Naujokat (SpringerOpen, 2022)
Abstract Purpose Dental implant surgery was developed to be the most suitable and comfortable instrument for dental and oral rehabilitation in the past decades, but with increasing numbers of inserted implants, complications are becoming more common. Diabetes mellitus as well as prediabetic conditions represent a common and increasing health problem (International Diabetes Federation in IDF Diabetes Atlas, International Diabetes Federation, Brussels, 2019) with extensive harmful effects on the entire organism [(Abiko and Selimovic in Bosnian J Basic Med Sci 10:186-191, 2010), (Khader et al., in J Diabetes Complicat 20:59-68, 2006, https://doi.org/10.1016/j.jdiacomp.2005.05.006 )]. Hence, this study aimed to give an update on current literature on effects of prediabetes and diabetes mellitus on dental implant success. Methods A systematic literature research based on the PRISMA statement was conducted to answer the PICO question "Do diabetic patients with dental implants have a higher complication rate in comparison to healthy controls?". We included 40 clinical studies and 16 publications of aggregated literature in this systematic review. Results We conclude that patients with poorly controlled diabetes mellitus suffer more often from peri-implantitis, especially in the post-implantation time. Moreover, these patients show higher implant loss rates than healthy individuals in long term. Whereas, under controlled conditions success rates are similar. Perioperative anti-infective therapy, such as the supportive administration of antibiotics and chlorhexidine, is the standard nowadays as it seems to improve implant success. Only few studies regarding dental implants in patients with prediabetic conditions are available, indicating a possible negative effect on developing peri-implant diseases but no influence on implant survival. Conclusion Dental implant procedures represent a safe way of oral rehabilitation in patients with prediabetes or diabetes mellitus, as long as appropriate precautions can be adhered to. Accordingly, under controlled conditions there is still no contraindication for dental implant surgery in patients with diabetes mellitus or prediabetic conditions.